ANALISIS PENCEMARAN KUALITAS KIMIA AIR SUMUR DANGKAL DI PERMUKIMAN KUMUH RW IV KELURAHAN BANGKA JAKARTA SELATAN - El Muzdalifa; Nurjazuli Nurjazuli; Tri Joko (Jurnal Kesehatan Masyarakat (Undip), 2022)
Use of groundwater as a water source in South Jakarta is quite high with a usage value of 3,768,226 m3. Most of the shallow groundwater in RW IV Bangka village are at a depth of <25 mbgl, so they have the potential to be polluted.. Moreover that village categorized as slums area, where there is high risk to be polluted by poor environment. . This study aims to analyze the level quality of Fe and CaCO3 pollution and their correlation with the risk factors in shallow well water in RW IV Bangka Village. This type of research is analytic observational with a cross sectional approach. The research population was the total number of wells in the residential area of RW IV, with the research sample using purposive random sampling of 30 shallow wells. The results showed that 100% of the samples met the requirements for pH (x̄= 8,0) and CaCO3 (x̄= 253 mg/l) levels. Meanwhile, for Fe (x̄= 0,29 mg/l) value , there were 7 samples (23,2%) that did not meet the requirements. Chi-square statistical analysis showed that there was no relationship between latrine distance (p=0,666), distance of other pollutants (p=0,675), standing water around the well (p=1,00), and SPAL conditions (p=0,304) with the Fe quality in shallow well water. However, based on the prevalence ratio (PR), the highest risk was found in other pollutant distance factors compare to others (PR=1,524).  The conclusion that, although the levels of Fe and CaCO3 in shallow well water are quite high, statistical analysis shows that there is no correlation from environment risk factors for these two value levels by reason, most of well type for sampling is bore well type which is low for contamination.